Inicjatywy gospodarcze Rostworowskich (1865–1934) w Milejowie na Lubelszczyźnie - Rostworowski, Stanisław Jan (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The first initiator of the industrial activity was Antoni Ignacy Rostworowski who owned a cigarette and cigar manufacture, probably between 1860 and 1873. He closed the plant after becoming indebted at Jewish merchants from Lublin and Łęczna. His son, Antoni Jan, opened a mill, spirit distillery and dairy cooperative in Milejów and brick plant in Starościce. But the real impulse for economic development of Milejów was establishing in 1907–1908 the sugar refinery (registered as joint stock company), that employed 160 people. Establishing of the factory resulted in intensifying agriculture production (white beet plantations), cattle breeding (Dutch cows) and development of housing. The sugar company survived until 1935, when during the economic depression it was merged with Lublin sugar refinery.